Controlling electron transport towards efficient all-solution-processed quantum dot light emitting diodes. Issue 21 (18th May 2022) - Chen, Hongting; Ding, Ke; Fan, Lianwei; Zhang, Rui; Guo, Runda; Zhang, Jibin; Hou, Lintao; Wang, Lei
Abstract : A high maximum external quantum efficiency of an all-solution-processed quantum dot light-emitting diode is demonstrated to be 28.6% by tailoring the electron injection for balancing the charge injection in a QLED. Abstract : Zinc oxide nanoparticles (ZnO NPs) are widely used as electron transport materials in all-solution-processed quantum dot light-emitting diodes (QLEDs), owing to their good stability, high electron mobility, and desirable energy levels with the neighboring quantum dot (QD) layer. However, the overall performance of QLEDs is always strictly limited by the imbalanced charge injection with lower hole injection from the neighboring hole transport layer into QDs, which motivates us to focus on the electron transport of ZnO NPs to tailor the charge balance in QLEDs. In this work, an ethanolamine (EA) treatment method is introduced to tune the defect density, electrical properties and morphology of ZnO NPs. By introducing a rational EA layer into ZnO NPs, the electron injection in the QLED device is suitably impeded and then the charge balance is improved, resulting in an efficient QLED with a low turn on voltage of 1.75 V and a high-power efficiency (PE) of 52.3 lm W −1, corresponding to an external quantum efficiency (EQE) of 28.6%, which is one of the highest values among QLEDs. Our work provides a simple and effective approach for tuning the electron transport and injection, which can also be used in other optoelectronic devices.